IMPACT OF WORKSHOPS ON THEMES OF WORLD AIDS DAYS - Saeed, Abdul Karim; Siddiqui, Noaman; Inayat, Azeem (Journal of Ayub Medical College Abbottabad, 2001)
Background: Abbottonians Medical Association®, Abbottabad, Pakistan in collaboration with UNAIDS Pakistan arranged two Workshops, the first in 1999, the Theme of which was Listen, Learn, Live", and the second in the year 2000 with Men Make Difference as the Theme. The aim of these workshops was to create awareness amongst the participants regarding H1V/AIDS. Objectives: We used the data of the above-mentioned workshops to analyze the gain in knowledge and attitudes of the participants, with an idea to develop recommendations for the use of such workshops for increasing the awareness regarding HIV/AIDS. Methods: The data of the two above-mentioned workshops were used to assess the percentage gain in knowledge and attitudes of the participants. We also compared our results with the contemporary studies and developed our recommendations. Results: The results show highly significant (p <.001) increase in the HIV/AIDS related knowledge and attitudes in the participants of these workshops. This difference was more significant in the teachers as compared to the students, showing a higher level of awareness in the youngsters. The net gain in the knowledge was very significant. The knowledge about HIV spread increased by 28.96 % for the students and 19.54 % for the teachers, while the net gain in attitudes was 36.16 % for the students and 71.43 % in the teachers. Conclusions: Short workshops on the Themes of World AIDS Days are very beneficial for improvement in the level of awareness for HIV/AIDS prevention and control.